Tree Diversity Enhances Nitrogen Retention and Accelerates Phosphorus Cycling - Tao Wang; Zaipeng Yu; Minghui Da; Mengjuan Wang; Hui Jia; Lulu He; Xiaohua Wan; Zhiqun Huang; Yann Hautier (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) cycling are crucial for terrestrial ecosystem productivity and carbon sequestration. While biodiversity is known to regulate soil N and P availability, the mechanistic linkages between biodiversity and fundamental processes of nutrient cycles remain unclear. This knowledge gap limits our capacity to model ecosystem biogeochemical responses to biodiversity loss. Using a large‐scale tree diversity experiment in subtropical China, we examined how tree species richness regulates ecosystem nutrient cycling in a region with N sufficiency but P limitation. We found that increased tree species richness enhanced N retention by boosting plant N stock and recycling, while reducing soil NO 3 − leaching and N 2 O emissions. These shifts, coupled with a reduction in soil δ 15 N, demonstrate tighter N cycling. Concurrently, tree species richness increased soil acid phosphatase activity, foliar P resorption efficiency, and plant P storage, synergistically accelerating ecosystem P cycling. Our integrated findings provide direct experimental evidence that tree diversity regulates both N and P cycling, offering valuable insights into how plant diversity can mitigate nutrient imbalances and promote ecosystem resilience to nutrient limitations.